Space in Ancient Greek Literature Studies in Ancient Greek Narrative, Volume Three - de Jong, Irene J.F (Mnemosyne, Supplements, 2012)
The third volume of the Studies in Ancient Greek narrative deals with the narratological category of space: how is space, including objects which function as 'props', presented in narrative texts and what are its functions (thematic, symbolic, psychologising, or characterising).; Readership: All those interested in ancient Greek literature, narrative theory, literary history, comparative literature.